2016
DOI: 10.1159/000443531
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Cellular Expression of IL-17 by CD4+ T-Cells in Osteoporotic Postmenopausal Women

Abstract: Aim: The study aimed to investigate cellular expression of IL-17 by CD4+ T-cells in osteoporotic postmenopausal women. Methods: We enrolled 25 postmenopausal women with osteoporosis (PostMO) and 25 postmenopausal women with normal bone mineral density measurements (PostM) to examine the production of IL-17, tumor necrosis factor a (TNFa) and receptor activator of nuclear factor γ-B ligand (RANKL) by CD4+ T-cells and IL-17, RORγt, TNFa and RANKL mRNA levels in CD4+ T-cells. Circulating concentrations of IL-17 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Although aspects of these findings such as the increase in IL‐7, IL‐15, and IL‐17A have been noted to increase post‐OVX in mice and in postmenopausal women with osteoporosis, our study connects the cellular and signaling components into a coherent description. The role of DCs and FasL have also been previously noted .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although aspects of these findings such as the increase in IL‐7, IL‐15, and IL‐17A have been noted to increase post‐OVX in mice and in postmenopausal women with osteoporosis, our study connects the cellular and signaling components into a coherent description. The role of DCs and FasL have also been previously noted .…”
Section: Discussionmentioning
confidence: 91%
“…Pioneering studies by Roggia and colleagues showed that in mice, ovariectomy (OVX) leads to increased TNFα‐producing T cells in the bone marrow. Furthermore, whereas postmenopausal women with normal bone density have undetectable levels of IL‐17A, postmenopausal osteoporotic women have detectable levels of IL‐17A in peripheral blood . Together, these results suggest that low‐grade inflammation promotes or is associated with bone loss in some postmenopausal women.…”
Section: Introductionmentioning
confidence: 98%
“…These T EFF are detected in the BM at earlier time points but could be detected in peripheral blood at 90 days in untreated mice (Figure 3). These T cells producing TNFα, IL-6, and IL-17A have been observed in postmenopausal osteoporotic women (47) and may contribute to other comorbidities such as mood disorders, joint pain, and atherosclerosis observed in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α leads to cell migration towards the infected and inflamed site, inducing the upregulation of adhesion molecules and production of chemotactic chemokines. [ 4 5 ] It plays a central role in inflammatory reaction, bone resorption, and loss of connective tissue. It further upregulates the production of other proinflammatory innate immune cytokines such as IL-1β and IL-6.…”
Section: Introductionmentioning
confidence: 99%
“…It further upregulates the production of other proinflammatory innate immune cytokines such as IL-1β and IL-6. [ 4 5 6 ] The latter are involved in inflammatory cell migration and osteoclastogenic process. [ 6 7 ] Absence of innate immunity cytokines attenuates inflammatory bone loss but their simultaneous inhibition results in more effective protection leading to almost complete remission of bone loss.…”
Section: Introductionmentioning
confidence: 99%